Annual reviews of computational physics V (World Scientific, 1997)
In this fifth volume of the authoritative series, the simulation of forest fires, flames, and hydrodynamics is presented in the first three articles. The next two deal with quantum simulations, in particular for two dimensions (quantum Hall effect and monolayers). Biology is connected with the last two articles: we learn from biological evolution to complement computer hardware and software with evolware, or we simulate immunology.